Diverse Partitiviruses From the Phytopathogenic Fungus, Rosellinia necatrix - Telengech, Paul; Hisano, Sakae; Mugambi, Cyrus; Hyodo, Kiwamu; Arjona-López, Juan Manuel; López-Herrera, Carlos José; Kanematsu, Satoko; Kondo, Hideki; Suzuki, Nobuhiro (Frontiers in Microbiology, 2020)
Partitiviruses (dsRNA viruses, family Partitiviridae) are ubiquitously detected in plants and fungi. Although previous surveys suggested their omnipresence in the white root rot fungus, Rosellinia necatrix, only a few of them have been molecularly and biologically characterized thus far. We report the characterization of a total of 20 partitiviruses from 16 R. necatrix strains belonging to 15 new species, for which Rosellinia necatrix partitiviruses 11 to 25 were proposed, and 5 previously reported species. The newly identified partitiviruses have been taxonomically placed in two genera, Alphapartitivirus, and Betapartitivirus. Some partitiviruses were transfected into reference strains of the natural host, R. necatrix, and an experimental host, Cryphonectria parasitica, using purified virions. A comparative analysis of resultant transfectants revealed interesting differences and similarities between the RNA accumulation and symptom induction patterns of R. necatrix and C. parasitica. Other interesting findings include the identification of a probable reassortment event and a quintuple partitivirus infection of a single fungal strain. These combined results provide a foundation for further study aimed at elucidating mechanisms that underly the differences observed.